Three new species of Valeriana (Valerianoideae, Caprifoliaceae) from southern Ecuador - Persson, Claes; Eriksen, Bente; Pérez, Álvaro J.; Zapata, J. Nicolás; Couvreur, Thomas L.p.; Sklenář, Petr (Phytotaxa, 2023)
Three new species of Valeriana from southern Ecuador are described and illustrated. Valeriana plateadensis is found near the highest peak of Cerro Plateado in Cordillera del Cóndor at 2900 m a.s.l. and is recognized by the shrubby habit and sessile, densely imbricate, spatulate leaves and 3-lobed corollas. V. yacuriensis is found near Lagunas Negras de Jimbura in the Parque Nacional Yacurí at 3500 m a.s.l. and is recognized by the shrubby habit, petiolate leaves and 3-lobed corollas. V. xenophylloides is found in the Páramo de Patococha at 3400 m a.s.l. and is recognized by its cushion growth form, the crown of trichomes at the leaf apex and 3-lobed corollas.